THE DETERMINANTS OF FIRM VALUE OF PROPERTY AND REAL ESTATE COMPANIES IN INDONESIA - Atmojo, Adrian Tri; Wijayanti, Anita; Siddi, Purnama (Jurnal RAK (Riset Akuntansi Keuangan), 2024)
This study aims to examine and analyze the influence of profitability, liquidity, leverage, and stock prices on the firm value of property and real estate companies in Indonesia. The population in this study consists of 92 property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2022. The sample selection technique in this study uses purposive sampling. The sample used in this research consists of 19 companies over four consecutive years. The data analysis technique used in this study employs multiple linear regression analysis. Based on the test results conducted on the variables influencing the value of the companies, it can be concluded that liquidity, leverage, and stock prices have a positive effect on firm value. Meanwhile, profitability does not affect the value of the companies.